2007 IEEE Internatonal Conference on Mobile Adhoc and Sensor Systems 2007
DOI: 10.1109/mobhoc.2007.4428743
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Data Aggregation and Reliability in Managing Wireless Sensor Networks

Abstract: Using data aggregation to reduce power consumption is a well studied area. In this paper we show a new result: data aggregation can also be used to increase reliability.In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The maximum number of transmits is set to an integer value that enables the non-aggregated case to meet the required reliability of delivery of all the data to the root node (of 99%). The maximum transmissions is increased by a factor consisting of the number of data elements*the policy factor for aggregated data (to reflect the increased value of the data) as shown in [10]. In each case, the data delivered by the sensing nodes is 1 Byte long, and a packet overhead of Table III), the results show the large number of packets required for every data packet to be delivered separately up the tree in the non-aggregated case.…”
Section: A Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum number of transmits is set to an integer value that enables the non-aggregated case to meet the required reliability of delivery of all the data to the root node (of 99%). The maximum transmissions is increased by a factor consisting of the number of data elements*the policy factor for aggregated data (to reflect the increased value of the data) as shown in [10]. In each case, the data delivered by the sensing nodes is 1 Byte long, and a packet overhead of Table III), the results show the large number of packets required for every data packet to be delivered separately up the tree in the non-aggregated case.…”
Section: A Numerical Resultsmentioning
confidence: 99%
“…As shown in [10], packets containing multiple, aggregated data values require an increased retransmission limit in order to provide high reliability (i.e. high percentage of data delivery).…”
Section: A Variables and Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in free space, it is shown that the power a receiver receives is proportional to the wavelength of the signal (λ) and the height of antennas (H) [17]. The distance (D) between the transmitter and receiver also influences the reliability of the WSNs [15]. The environment coefficient (C E ) parameter was chosen to resolve the complex influence of environmental factors in the communications quality for the WSNs [16,17].…”
Section: Selected Parametersmentioning
confidence: 99%
“…Data aggregation in the proposed framework involves gathering data points, analyzing, reporting, and transforming them into a manageable format. Hence the main aim of data aggregation is to increase reliability [45].…”
mentioning
confidence: 99%